Applied nonlinear programming - Sharma, Sanjay (New Age International, 2006)
The present book explains the applied nonlinear programming, which has wide spread scientific and industrial applications. Salient features One variable optimization Unconstrained and constrained optimization Geometric programming Multi-variable optimization The book is a useful reference/text for practitioners/students.